A Comparative Study of Bacillus Spp. Isolated from Various Sources and Commercial Food Supplements and Evaluation of Some Probiotic Properties - Kahraman, Burcu; Senol, Burcu Mine; Dertli, Enes; Arici, Muhammet (UNIV NAMIK KEMAL, 2024)
Bacillus species are gram-positive, aerobic, peritrically flagellated and endospore-forming bacteria. They can be found everywhere in the environment, especially in soil (its common habitat), water, dust or in the air. Probiotics, which have beneficial health effects, constitute an important group of Bacillus species. This study aimed to isolate Bacillus from various sources, identify it molecularly and determine its probiotic properties. For this purpose, eight Bacillus subtilis, Bacillus coagulans and Bacillus clausii strains among 58 isolates from fish intestine, soil, ripened cheese and commercial probiotic supplements were identified and their probiotic properties were characterized. Firstly, Bacillus strains were molecularly identified by 16S rRNA PCR analysis. The growth of Bacillus isolates at various temperatures, salt concentrations, and pH levels, as well as tests for esculin hydrolysis, starch hydrolysis, nitrate reduction, and gas generation from glucose, were all investigated to assess the isolates' physiological and biochemical characteristics. In terms of probiotic potential of Bacillus isolates; tolerance of bile salt, cell surface hydrophobicity, auto aggregation, antibiotic susceptibility tests were conducted. In all analyses, strains obtained from food supplements showed high levels of hydrophobicity and auto-aggregation properties, and the highest values following these strains were observed in Bacillus subtilis strains (F1 and S2) isolated from fish intestines and soil, respectively. All strains showed strong growth features in bile salt conditions. It has been determined that antibiotic sensitivity varies depending on the strain. Overall, high sensitivity to tetracycline has been observed. In summary, this study revealed the potential probiotic properties of Bacillus isolates obtained from different sources. The study also compared these probiotic properties with probiotic Bacillus strains isolated from food supplements.
Keywords: Bacillus; Biochemical characterization; Molecular identification; Probiotics; LACTIC-ACID BACTERIA; BIOLOGICAL-CONTROL; STRAINS; ADHESION; ABILITY; TRACT; Agriculture